Global science & technology information : a new spin on access - Wagner, Caroline S.; Yezril, Allison (Science and Technology Policy Institute, RAND, 1999)
In the more than 30 years the U.S. federal government has tracked and monitored international science and technology information (ISTI), the global marketplace and the economy have changed dramatically. Capabilities in other nations have matured, resulting in highly competitive products. The RAND survey described here suggests that there is a need for timely, unbiased, global, and easily accessible ISTI, that government collection and analysis of that information are and will continue to be important government roles, and that this need is likely to grow. Expanding the government's mission here would greatly enhance and update the services provided to all users. Possible improvements include providing a global overview, adding economic and trade information, encouraging networking of information and resources, and increasing the number of quick responses and person-to-person interactions. Many of these improvements can, in fact, take advantage of the globalization of industry, the information revolution, and dispersed scientific excellence. The effective features of existing services, combined with new information tools and opportunities, can be incorporated to build the next generation of ISTI services.